2023
DOI: 10.1371/journal.ppat.1011274
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of African-lineage Zika virus through the fetal membranes in a rhesus macaque (Macaca mulatta) model

Michelle R. Koenig,
Ann M. Mitzey,
Xiankun Zeng
et al.

Abstract: Zika virus (ZIKV) can be transmitted vertically from mother to fetus during pregnancy, resulting in a range of outcomes including severe birth defects and fetal/infant death. Potential pathways of vertical transmission in utero have been proposed but remain undefined. Identifying the timing and routes of vertical transmission of ZIKV may help us identify when interventions would be most effective. Furthermore, understanding what barriers ZIKV overcomes to effect vertical transmission may help improve models fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 60 publications
2
13
1
Order By: Relevance
“…Steroid hormones in serum were assessed by the Wisconsin National Primate Research Center's Assay Services Unit using a Roche Cobas e411 analyzer as previously described 15 .…”
Section: Hormone Assaysmentioning
confidence: 99%
“…Steroid hormones in serum were assessed by the Wisconsin National Primate Research Center's Assay Services Unit using a Roche Cobas e411 analyzer as previously described 15 .…”
Section: Hormone Assaysmentioning
confidence: 99%
“…A strong pro-inflammatory response to infection mounted by decidual leukocytes could contribute to adverse pregnancy outcomes. In vivo and ex vivo studies have demonstrated that ZIKV readily infects the decidua ( 28 36 ). The acute decidual response to ZIKV infection remains essentially unstudied in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…showed that African-lineage ZIKV can be vertically transmitted through the fetal membranes during early pregnancies in rhesus macaques ( 36 ). African-lineage ZIKV was used in that study because it consistently produced a high rate of vertical transmission, an ideal result for a macaque model with limited animal numbers ( 36 ). Koenig et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations